Pengaruh Profitabilitas Terhadap Harga Saham Pada Perusahaan Rokok Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2015-2021 - Helena Jayanti; Antonius Philippus Kurniawan; Cicilia Ayu Wulandari Nuwa (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was condycted to (1) determine the description of Return On Asset (ROA), E arning Per Share (EPS), and the stock prices of cigarette companies listed on the Indonesia Stock Exchange, (2) determine the effect of Return On Asset (ROA) and Earning Per Share (EPS) partially on the stock prices of cigarette companies listed on the Indonesia Stock Exchange, (3) ) determine the effect of Return On Asset (ROA) and Earning Per Share (EPS) simultaneously on the stock prices of cigarette companies listed on the Indonesia Stock Exchange. The data used in this research were secondary data. The research population was five cigarette companies listed on the Indonesia Stock Exchange in 2015-2021 with the sampling technique used was purposive sampling. Quantitative research method with associative descriptive approach. Hypothesis testing was done through the t-test and f-test. The data analysis used multiple linear regression. The results of data analysis showed that partially, the variables Return On Asset (ROA) and Earning Per Share (EPS) had a significant effect on stock prices. While simultaneously, the variables Return On Asset (ROA) and Earning Per Share (EPS) had a significant effect on stock prices. As much as 23,4% of the variance in the stock prices variable was explained by the independent variables, while 76,6% was influenced by other factors excluded from the research variables.